Achieving ethnic equality in the Israel trauma healthcare system: the case of the elderly population - Nura Abdel-Rahman; Nechemia Yoffe; Maya Siman-Tov; Irina Radomislensky; Israel Trauma Group; Kobi Peleg (BMC, 2019)
Abstract Objective To determine if ethnic disparities exist with regard to the risk of injury and injury outcomes among elderly hospitalized casualties in Israel. Methods A retrospective study based on data from the Israeli National Trauma Registry between 2008 and 2017. Data included demographic, injury and hospitalization characteristics. Descriptive statistics and adjusted logistic regression were used to examine the differences between Jewish and Arab casualties, aged 65 and older. Result The study included 96,795 casualties. The proportion of elderly hospitalized casualties was 2.8 times greater than their proportion in the population (3.1 times greater among Jews and 2.1 times among Arabs). In comparison to Arabs, Jews suffered from a greater percentage of head injuries (10.5 and 8.9%, respectively for Jews and Arabs p < .001), but fewer extremity injuries (46.7% vs. 48.0% respectively for Jews and Arabs p < .05). Among severe/critical casualties and among casualties with severe head injuries, Arabs were more likely to be transported to the hospital in a private car (27% vs. 21% respectively for Arabs and Jews p < .001; 30.5% vs. 23.3% respectively for Arabs and Jews p < .001). Logistic regression analysis, adjusted for age, gender, injury severity, type of injury, type of trauma center and year of admission, shows that Jews, relative to Arabs, were more likely to be hospitalized for more than seven days, admitted to the intensive care unit (ICU) and to be discharged to a rehabilitation center (OR: 1.3, 1.3 and 2.4 respectively). No differences regarding surgery (OR: 0.95) or in-hospital mortality (OR: 0.99) were found. Conclusions Ethnic disparities between Jewish and Arab hospitalized casualties were observed with regard to hospital stay, ICU admission and rehabilitation transfer. However, no differences were found with regard to mortality and surgery. While the reported disparities may be due in part by cultural differences and accessibility, health policy decision makers should aim to reduce the gaps by optimizing the accessibility of ambulance and rehabilitation services as well as increasing awareness regarding the availability of these medical services among the Arab population.